Corporate Policy Considerations in Implementing 1.1% and 11% VAT on Coffee Sales - M. Aziz Fatur Rachman; Agus Zahron Idris; Ratna Septiyanti; Niken Kusumawardani (Riset Akuntansi dan Bisnis Indonesia, 2026)
Purpose: This study aims to analyze the conformity of the implementation of Value Added Tax (VAT) on the sale of unprocessed coffee beans and examine the company’s policy considerations in selecting the applicable VAT rate at PT Arga Bumi Indonesia. Methodology: This study employed a case study approach with data collection methods conducted through observations, interviews, and documentation of sales transactions, tax invoices, and the tax administration system implemented by the company. Results: PT Arga Bumi Indonesia applies the 11% standard VAT rate in compliance with tax regulations, despite the availability of a 1.1% VAT scheme for certain agricultural products such as processed coffee. This choice is driven by customer characteristics, as most buyers are Taxable Entrepreneurs who require input VAT credit. Conclusion: The company’s policy on applying the VAT rate considers not only administrative convenience but also the needs of business partners, legal certainty, and the sustainability of the company’s business relationships. Limitations: This study is limited to a single company and focuses only on the implementation of VAT on Certain Agricultural Products (BHPT), specifically the sale of dried and roasted coffee beans. Therefore, the findings may not fully represent other agricultural sectors or companies with different characteristics. Contribution: This study contributes to the understanding of VAT implementation in the agricultural sector and provides practical insights for companies in determining VAT policies that align with tax regulations and with business needs.